A review of the genus Haemonides Hübner, [1819] (Lepidoptera: Castniidae) - Worthy, Robert; González, Jorge M.; Lamas, Gerardo (Zootaxa, 2017)
The giant butterfly-moths (Castniidae: Castniinae) are distributed in the Neotropics from Mexico, throughout Central America, down to South America reaching Argentina and Chile. Among the highly diverse genera, Haemonides Hübner is particularly striking due to the white or cream ground colour of their wings outlined with black margins which give it a vague resemblance to some species of Pieridae. Several species and subspecies have been described but research studies and information on the genus are scarce and in some cases confusing. In this work, the genus Haemonides, restricted to South America, is revised and the diagnostic phenotypic characteristics of males and females, as well as male genitalia are illustrated. Details on its history, biogeography and biology are included with the purpose of solving the confusion in identifying the species of the genus. A neotype is designated for Papilio cronis Cramer and a lectotype for Castnia cronida Herrich-Schäffer. A new subspecies H. cronis vinciguerrrai ssp. nov. is described. Other taxa are revised and their taxonomic and nomenclatural status clarified.